Pemberdayaan Ekonomi Rumah Tangga Melalui Optimalisasi Keuangan Sederhana dan Pembuatan ZPT Organik Berbasis Lingkungan - Reinati, Stefanus; Vidensia Bergita Anin; Naisanu, Joritha; Henny A. Raga; Darmanto F. Kisse; Delorens L.N. Bessie; Richart Oematan; Lukas Billy (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service activity was carried out in Mata Air Village on July 19, 2025, with the aim of empowering household economies through two main approaches: basic financial literacy education and training in the production of environmentally friendly organic Plant Growth Regulators (PGR). The program was initiated in response to the low level of financial literacy among villagers and the underutilization of local resources to support sustainable agriculture. The method involved needs assessment, contextual material design, implementation through interactive lectures and hands-on practice, and participatory evaluation. The results showed that participants gained new insights into managing household finances and were able to independently produce organic PGR using local materials. Moreover, the activity sparked community initiatives to develop follow-up training and explore micro-business opportunities. This program demonstrates that a simple, practical, and contextual educational approach can have a positive impact on improving both economic capacity and environmental awareness in rural communities